Hemodynamic and Pressor Responses to Combination of Yoga and Blood Flow Restriction - Wooten, Savannah V.; Stray-Gundersen, Sten; Tanaka, Hirofumi (International Journal of Sports Medicine, 2020)
A combination of yoga and blood flow restriction, each of which elicits marked pressor responses, may further increase blood pressure and myocardial oxygen demand. To determine the impact of a combination of yoga and blood flow restriction on hemodynamic responses, twenty young healthy participants performed 20 yoga poses with/without blood flow restriction bands placed on both legs. At baseline, there were no significant differences in any of the variables between the blood flow restriction and non-blood flow restriction conditions. Blood pressure and heart rate increased in response to the various yoga poses (p<0.01) but were not different between the blood flow restriction and non-blood flow restriction conditions. Rate-pressure products, an index of myocardial oxygen demand, increased significantly during yoga exercises with no significant differences between the two conditions. Rating of perceived exertion was not different between the conditions. Blood lactate concentration was significantly greater after performing yoga with blood flow restriction bands (p=0.007). Cardio-ankle vascular index, an index of arterial stiffness, decreased similarly after yoga exercise in both conditions while flow-mediated dilation remained unchanged. In conclusion, the use of lower body blood flow restriction bands in combination with yoga did not result in additive or synergistic hemodynamic and pressor responses.
Keywords: exaggerated blood pressure response; isometric exercise; ischemia-reperfusion; endothelial function